Tujuan Manusia dan Jalan untuk Mencapainya Menurut Advaita Vedanta - Anak Agung Raka Asmariani (Sanjiwani: Jurnal Filsafat, 2021)
Humans are social creatures and in social life and have various complex problems. Various problems that exist are very difficult to be solved. Sometimes it is very difficult for humans to focus themselves to find what is really sought in this life so that a thought arises what is the purpose of humans living in this world? In this study Vedanta philosophy is able to answer this question. This study discusses "Human Goals and the Way to Achieving It According to Advaita Vedanta". This research is a qualitative research Hermeneutics then the data will be analyzed using descriptive and interpretative methods. This study found that the human goal is to achieve happiness, life and alive is a human goal towards a higher goal. In the teachings of Advaita Vedanta it is emphasized that to achieve the highest goal, namely Brahman itself, there are several ways that humans can take, namely: 1). Understanding Life and alive, 2). Understanding Reincarnation is a way to repair bad karma in previous lives in the hope that human goals will be achieved. 3). The four paths to the ultimate goal are: Karma Yoga, Jnana Yoga, Bhakti Yoga and Raja Yoga. Karma yoga is the way to do good actions between humans, helpful and work hard everytimes for the goodness, Jnana Yoga means to achieve the goal from education or knowledgment tha the human is a holly creature, Bhakti Yoga is the way to achieve the goal from the higher lovely to the God than the humans, and Raja Yoga is the way to achieve focuse on mind concentration.